Relationship between Spiritual Health and Quality of Life in University Students of Arak City - Ali Jadidi; Soleiman Zand; Ali Khanmohamadi Hezave; Negin Hosseini (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Quality of life is one of the most influential issues that can encourage a person to continue a happy and healthy life. On the other hand, spiritual health is one of the dimensions of health and a sense of harmonious connection between oneself, others, nature, and beyond, and leads to understanding the ultimate purpose and meaning in life. The purpose is to determine the relationship between spiritual health and quality of life in university students in Arak. The results of this study can be used to formulate strategic plans improve spiritual health and the quality of students' lives. Methods: First, the population of each university in Arak city was measured, and taking into account their population and establishing a ratio between the sample size of the study and the population of each university, people who had the characteristics of entering the study were included in the study. The sample size was 400 people and was conducted on students who have been studying at the university for at least six months. After obtaining the consent of the participants, the researchers filled out the questionnaire through interviews with the students. The questionnaires included two instruments: a spiritual health questionnaire and a quality of life questionnaire with 36 questions. Results: No significant relationship was observed between spiritual health and demographic variables. Likewise, spiritual health had no statistically significant relationship with demographic variables. The analysis of the study data showed that there is a positive correlation between the quality of life and spiritual health of students. (P < 0.05). Conclusions: According to the horoscope results, there is a relationship between the quality of life and the spiritual health of the students of Arak universities. By improving the quality of students' lives, we can increase their spiritual health, and even by increasing their spiritual health, we can witness the improvement of students' quality of life.